PUBLIC POLICIES FOR SCIENCE, TECHNOLOGY, AND INNOVATION IN BRAZIL FROM 2000 TO 2023: A STUDY OF THE STATE'S PERFORMANCE - Alencar, Antônio Idilvan Lima; Ferreira, Marcello (Seven Editora, 2025)
This article presents a bibliographic study of the Brazilian State’s role in formulating and implementing science, technology, and innovation (ST&I) policies from the year 2000 to the present. It is grounded in the premise that the State regulates, promotes, implements, and evaluates programmatic actions through legal, budgetary, and administrative mechanisms—such as Law No. 8,958/1994 and Law No. 9,394/1996—which make the development of ST&I possible. The main objective is to provide a brief contextualization of key public policies during this period and to investigate the extent to which these interventions have contributed to the national advancement of ST&I. The study draws on conceptual discussions about science, technology, innovation, the State, and public policy, based on legal documents, public programs, institutional frameworks, and academic studies (Cavalcante, 2011; Negri, 2021; Ferreira, Silva & Verdeaux, 2018; Tuchi, Morais & Pinho, 2017), with particular attention to financing mechanisms. The findings highlight that public policies and investments in ST&I are essential for social development, especially in improving the population’s living conditions. However, discontinuity and centralized governance models that overlook sufficient and diversified funding can hinder innovation-based progress. Thus, smart and consistent investment strategies are necessary to ensure the effectiveness and impact of these policies.DOI: https://doi.org/10.56238/sevened2025.029-024